Pelaksanaan Eksekusi Putusan Pengadilan Terhadap Sebagian Obyek Eksekusi Yang Dikuasai Pihak Ketiga - Riswanda Harvianto; Heri Hartanto, S.H., M.H (Sebelas Maret University, 2019)
This study aims to determine the process of court verdict execution on the object of execution controlled by third parties and the obstacles that experienced in executing the verdict and the solution to the verdict Number 30 / Pdt.G / 2009 / PN.Ska Jo Number: 347 / Pdt / 2009 / PT.Smg Jo Number: 1274K / Pdt /2010 Jo Number: 222PK / Pdt / 2015. This research is a descriptive empirical law research. The sources used in this study are primary legal materials and secondary legal materials. Data collection techniques used were feld studies at the Surakarta District Court and literature study, the main study in this study was Verdict Number: 30 / Pdt.G / 2009 /PN.Ska Jo Number: 347 / Pdt / 2009 / PT.Smg Jo Number : 1274K / Pdt / 2010 Jo Number: 222PK /Pdt/ 2015. The data analysis technique used is interactive analysis. Based on the results of research and discussion, concluded that the process of execution of the object controlled by a third party implemented by negotiation with the third party which ultimately resulted in the agreement of giving amends to third parties. Execution may be executed after a request for judicial review fled by the defendant and the resistance proposed by a third party is declared rejected. The obstacles experienced in executing the execution itself are from the frst judgment itself because, in consideration of the judge who decides at the frst level the so-called party to take control of the object of dispute the settlement may be done outside the court but, in its implementation the third party is resisting so that the execution process had experienced a delay.Keywords: Execution, Civil Verdict, Third Parties